Porous molecular cage modified perovskite solar cell and preparation method thereof
By doping porous molecular cages into perovskite materials, the interface contact of perovskite solar cells is improved, the interface defect problem is solved, and the carrier transmission efficiency and battery efficiency are improved.
Patent Information
- Application Number
- CN202510614013.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-13
- Publication Date
- 2025-08-15
AI Technical Summary
There are interface defects in perovskite solar cells, which lead to a decrease in open circuit voltage and filling factors, affecting battery efficiency.
Doping porous molecular cages in perovskite materials, the porous molecular cages are used to form chelation with iodine ions and lead ions in perovskite materials, improving interface contact and reducing the density of interface defect states.
It improves the efficiency of carrier extraction and transmission, enhances the interface contact between perovskite and the transport layer, and improves the open circuit voltage and photoelectric conversion efficiency of the battery.
Smart Images

Figure CN120500191A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic cell technology, and in particular to a porous molecular cage-modified perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have garnered significant research attention recently due to their high photoelectric conversion efficiency and low cost. However, various defects often exist in perovskite materials, which can reduce the open-circuit voltage and fill factor of the cell, thereby impacting its ultimate efficiency. While various methods have been developed to passivate these defects through interface modification, their effectiveness has been limited and further improvement is needed. Summary of the Invention
[0003] The main purpose of this application is to provide a porous molecular cage modified perovskite solar cell and a preparation method thereof to solve the problem of interface defects in the perovskite layer.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a porous molecular cage modified perovskite solar cell is provided, comprising a substrate layer, an electron transport layer, a modified photoactive layer, a hole transport layer and an electrode layer stacked in sequence; wherein the material of the modified photoactive layer is obtained by modifying the perovskite material by doping the porous molecular cage.
[0005] Furthermore, the porous molecular cage is a hydrazone-containing organic molecular cage.
[0006] Furthermore, the porous molecular cage is a lantern-shaped molecular cage formed by self-assembly of formylated calix[4]arene (C4RACHO) and dihydrazide through hydrazide bonds.
[0007] Furthermore, the porous molecular cage is selected from at least one of HPOC-101, HPOC-102, HPOC-103, HPOC-104, HPOC-201 and HPOC-301.
[0008] Furthermore, the weight doping ratio of the porous molecular cage material in the perovskite material is (0.1-1):(500-800); preferably (0.3-0.7):(600-700).
[0009] Furthermore, the thickness of the modified photoactive layer is 300 to 800 nm, preferably 400 to 700 nm, and more preferably 500 to 600 nm.
[0010] Furthermore, the molecular formula of the material of the modified photoactive layer is ABX3; wherein A is selected from CH3NH3 + 、NH3CH2NH3 + 、C8H9NH3 + 、Cs+ , Rb + and K + One or more of; B is selected from Pb 2+ 、Sn 2+ and Ge 2+ At least one of; X is selected from F - 、Cl - Br - and I - At least one of; preferably, A is CH3NH3 + and / or NH3CH2NH3 + ; B is Pb 2+ ; X is 1 - .
[0011] Furthermore, the conductive material of the base layer is ITO and / or FTO.
[0012] Furthermore, the material of the electron transport layer is at least one of SnO2, TiO2 and fullerene derivatives; preferably TiO2.
[0013] Furthermore, the material of the hole transport layer is at least one of Spiro-OMeTAD, PTAA and nickel oxide, preferably Spiro-OMeTAD.
[0014] Furthermore, the material of the electrode layer is at least one of Au, Ag, Cu and amorphous carbon, preferably Ag.
[0015] Furthermore, the thickness of the base layer is 100 to 400 nm, preferably 250 to 350 nm.
[0016] Furthermore, the thickness of the electron transport layer is 10 to 40 nm, preferably 25 to 35 nm.
[0017] Furthermore, the thickness of the hole transport layer is 30 to 300 nm, preferably 50 to 200 nm.
[0018] Furthermore, the thickness of the electrode layer is 20 to 300 nm, preferably 30 to 200 nm.
[0019] According to the second aspect of the present application, a method for preparing the porous molecular cage-modified perovskite solar cell is provided, comprising:
[0020] Provides a base layer;
[0021] coating an electron transport material on the surface of the base layer to form an electron transport layer;
[0022] Mixing the porous molecular cage material and the perovskite precursor solution to form a modified photoactive precursor solution; coating the modified photoactive precursor solution on the surface of the electron transport layer to form a modified photoactive layer;
[0023] coating a hole transport material on the surface of the modified photoactive layer and performing an oxidation treatment to form a hole transport layer;
[0024] The electrode material is deposited on the surface of the hole transport layer to form an electrode layer.
[0025] Furthermore, the concentration of the perovskite precursor solution is (500-800) mg / mL; preferably (600-700) mg / mL; the added concentration of the porous molecular cage material in the perovskite precursor solution is (0.1-1) mg / mL; preferably (0.3-0.7) mg / mL.
[0026] Furthermore, the perovskite precursor solution is a mixture of FAI, MACl, PbI2 and a solvent; preferably, the molar ratio of FAI, MACl and PbI2 is 1:(0.05-0.15):1; and the solvent is N,N-dimethylformamide.
[0027] Furthermore, the modified photoactive precursor solution is subjected to a second annealing after coating, and the temperature of the second annealing is 80-150°C.
[0028] Furthermore, the hole transport material is at least one of Spiro-OMeTAD, PTAA and nickel oxide; preferably Spiro-OMeTAD; further preferably, the hole transport material is also doped with Li-TFSI.
[0029] Furthermore, the conductive material of the base layer is ITO and / or FTO.
[0030] Furthermore, the electron transport material is at least one of SnO2, TiO2 and fullerene derivatives; preferably TiO2.
[0031] Furthermore, the electrode material is at least one of Au, Ag, Cu and amorphous carbon, preferably Ag.
[0032] Furthermore, the electron transport material is subjected to a first annealing after coating, and the temperature of the first annealing is 150-200°C.
[0033] Compared with the existing technology, this application has the following technical effects:
[0034] The above-mentioned porous molecular cage modified perovskite solar cell and its preparation method provided in the present application modify the perovskite material layer by doping the porous molecular cage material into the perovskite material layer; the above-mentioned porous molecular cage has a high specific surface area and rich functionalized sites, and can form a chelate effect with the iodide ions and lead ions in the perovskite, which can effectively improve the interface contact between the perovskite and the transport layer, reduce the interface defect state density, and improve the carrier extraction and transmission efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings, which constitute part of this application, are used to provide a further understanding of this application. The exemplary embodiments and descriptions of this application are used to explain this application and do not constitute an improper limitation on this application.
[0036] Figure 1 A schematic diagram of the structure of a perovskite solar cell prepared in an embodiment of the present application;
[0037] Figure 2 This is a JV characteristic curve of the perovskite solar cell prepared in Example 1 of the present application;
[0038] Figure 3 This is a JV characteristic curve of the perovskite solar cell prepared in Comparative Example 1 of the present application.
[0039] Reference numerals:
[0040] 1. Base layer; 2. Electron transport layer; 3. Modified photoactive layer; 4. Hole transport layer; 5. Electrode layer. DETAILED DESCRIPTION
[0041] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments in this application can be combined with each other. The present application will be described in detail below with reference to the embodiments.
[0042] As mentioned in the background art, various types of defects exist at the interface of the perovskite layer of the perovskite solar cell, which can cause the open circuit voltage and fill factor of the cell to decrease, thereby affecting the final photoelectric efficiency of the cell.
[0043] To solve the above problems, according to one aspect of the present application, a porous molecular cage modified perovskite solar cell is provided, such as Figure 1 As shown, it includes a base layer 1, an electron transport layer 2, a modified photoactive layer 3, a hole transport layer 4 and an electrode layer 5 stacked in sequence; wherein the material of the modified photoactive layer is obtained by modifying the perovskite material by doping a porous molecular cage.
[0044] The molecular cage material selected in this application is a new type of organic matter with excellent chemical stability and molecular structure designability. The carbonyl and amine groups in the molecular cage can interact with the defects in the perovskite material, passivating these defects, thereby improving the open circuit voltage and photoelectric conversion efficiency of the battery; the molecular cage material can be effectively dispersed in DMF solvent and has good compatibility with the perovskite preparation process. The porous organic molecular cage is doped into the perovskite material to modify it; the porous organic molecular cage has a high specific surface area and rich functional sites, which can form a chelate effect with the iodide ions and lead ions in the perovskite, which can effectively improve the interface contact between the perovskite and the transport layer, reduce the interface defect state density, and improve the extraction and transmission efficiency of carriers.
[0045] In some embodiments, the porous molecular cage is a hydrazone-containing organic molecular cage; for example, the porous molecular cage is a lantern-shaped molecular cage formed by self-assembly of formylated calix[4]arene (C4RACHO) and dihydrazide through hydrazide bonds; for another example, the porous molecular cage can be selected from at least one of HPOC-101, HPOC-102, HPOC-103, HPOC-104, HPOC-201, and HPOC-301.
[0046] The HPOC-type molecular cages of the present application can be selected from existing technologies or synthesized independently. For example, the synthesis method of HPOC-101 is as follows: C4RACHO (20 mg) and malonyl dihydrazide (6.6 mg) are added to DMF (3 mL) to form a mixture; the mixture is sealed in a 10 mL glass vial and heated at 100°C for 12 hours; after the solution evaporates for several hours, a bulk crystal of the molecular cage HPOC-101 is obtained. When synthesizing HPOC-102, HPOC-103, and HPOC-104, malonyl dihydrazide is replaced with succinyl dihydrazide, glutaryl dihydrazide, and adipic dihydrazide, respectively.
[0047] The nitrogen atoms in the amine group and the oxygen atoms in the carbonyl group of the above-mentioned type of molecular cage selected in this application can form stable coordination bonds with lead (Pb) ions, passivate vacancies or coordination unsaturated defects around the lead ions, reduce non-radiative recombination centers, and improve carrier lifetime and mobility; the carbonyl group can also interact with defects in the perovskite lattice, further stabilize the perovskite structure, reduce the defect density at the grain boundary, and improve the crystallinity of the film; this type of organic molecular cage has a high specific surface area and can provide more active sites to interact with defects in the perovskite, which helps to passivate defects more comprehensively; the doping of hydrazone-containing molecular cages can improve the interface contact between the photoactive layer and the electron transport layer and the hole transport layer, reduce charge recombination at the interface, and improve the charge extraction efficiency.
[0048] In some embodiments, the weight doping ratio of the porous molecular cage in the perovskite material is (0.1-1):(500-800); in this doping ratio, the weight ratio of the porous molecular cage can be any value of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or a range value between any two of them; in this doping ratio, the weight ratio of the perovskite material is any value of 500, 520, 550, 580, 600, 620, 650, 680, 700, 720, 750, 780, 800, or a range value between any two of them; for example, (0.3-0.7):(600-700); for another example, (0.4-0.6):(620-650); further 0.5:640. The above doping ratio refers to the ratio of the weight of the porous organic molecular cage material to the weight of the perovskite material in the modified photoactive film layer. Appropriate molecular cage doping can effectively passivate defects in the perovskite lattice, promote normal crystallization and film uniformity, reduce non-radiative recombination, and enhance carrier mobility, thereby increasing open-circuit voltage and fill factor. It also improves the contact between the perovskite layer and the electron transport layer or hole transport layer, promoting efficient charge extraction and transfer, and improving the overall efficiency of the battery.
[0049] In some embodiments, the modified photoactive layer 3 has a thickness of 300 to 800 nm; for example, the thickness is any value among 300, 400, 500, 600, 700, and 800 nm, or a range between any two thereof; for example, 400 to 700 nm; and another example, 500 to 600 nm. A perovskite layer of appropriate thickness can ensure effective absorption of photons across the entire visible to near-infrared spectrum, thereby improving photoelectric conversion efficiency. This thickness is beneficial for carrier diffusion length and transport efficiency, balancing carrier generation and transport efficiency. This thickness facilitates the rapid separation of photogenerated electrons and holes, reduces carrier transport losses, and promotes efficient charge transport. This thickness is more suitable for doping the perovskite material with an appropriate content of porous organic molecular cage material.
[0050] In some embodiments, the material of the modified photoactive layer 3 has a molecular formula of ABX3; wherein A is selected from CH3NH3 + 、NH3CH2NH3 + 、C8H9NH3 + 、Cs + , Rb + and K + One or more of; B is selected from Pb 2+ 、Sn 2+ and Ge 2+ At least one of; X is selected from F - 、Cl - Br- and I - At least one of; preferably, A is CH3NH3 + and / or NH3CH2NH3 + ; B is Pb 2+ ; X is 1 - The selected perovskite materials of the above type have good light absorption, which helps to absorb light and promote photoelectric conversion efficiency and stability. In addition, the above type of perovskite materials and the doped hydrazone-containing organic molecular cages have good synergistic effects and compatibility. The functional groups of the molecular cages can form coordination bonds with the B position in the perovskite, passivating lattice defects. The introduction of the molecular cages can enhance the coordination effect between the halogen ions and metal ions at the X position in ABX3. The presence of the molecular cages can introduce additional chemical bonds, stabilize the perovskite lattice, and improve the quality and stability of the composite film. The hydrazine and carbonyl groups in the hydrazone-containing molecular cages can form stable coordination or chelate structures with the halogen ions X and metal ions B in the perovskite lattice, which can significantly improve the crystallinity and stability of the perovskite layer, reduce the defect density, and thus improve the battery performance.
[0051] In some embodiments, the conductive material of the substrate layer 1 is ITO and / or FTO. The material of the electron transport layer 2 is at least one of SnO2, TiO2 and fullerene derivatives; preferably TiO2. The material of the hole transport layer 4 is at least one of Spiro-OMeTAD, PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) and nickel oxide; preferably Spiro-OMeTAD. The material of the electrode layer 5 is at least one of Au, Ag, Cu and amorphous carbon; preferably Ag. The selected substrate layer materials, electron transport materials, hole transport layer, and electrode layer materials all have good chemical stability, interface optimization, and charge transfer rate, which can significantly improve the photoelectric conversion efficiency and stability; the selection of the above-mentioned materials in each layer can optimize the performance of the perovskite solar cell to the greatest extent, including photoelectric conversion efficiency, physical stability, cost-effectiveness and compatibility.
[0052] In some embodiments, the thickness of the substrate layer 1 is 100 to 400 nm; for example, any value among 100, 150, 200, 250, 300, 350, and 400 nm, or any range therebetween; for example, 250 to 350 nm, and another example, 300 nm. The appropriate cathode layer thickness maintains good optical transparency, ensuring that most incident light can penetrate the perovskite layer without being excessively absorbed or scattered by the layer; provides good electrical conductivity to ensure efficient electron transport; and possesses sufficient mechanical strength and toughness.
[0053] In some embodiments, the thickness of the electron transport layer 2 is 10 to 40 nm; for example, the thickness is any value selected from 10, 15, 20, 25, 30, 35, or 40 nm, or any range therebetween; for example, 25 to 35 nm, and another example, 30 nm. An appropriate electron transport layer thickness facilitates rapid extraction and transport of electrons generated from the perovskite layer, reduces the probability of recombination during electron transport, and improves electron transport efficiency.
[0054] In some embodiments, the hole transport layer 4 has a thickness of 30 to 300 nm, such as any value among 30, 50, 80, 100, 120, 150, 180, 200, 230, 250, 270, or 300 nm, or any range therebetween, such as 50 to 200 nm, or 80 to 120 nm. An appropriate thickness can promote efficient hole migration from the perovskite layer to the hole layer, thereby improving hole mobility.
[0055] In some embodiments, the thickness of the electrode layer 5 is 20 to 300 nm, for example, any value selected from 20, 30, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, or 300 nm, or any range therebetween, for example, 30 to 200 nm, or another example, 80 to 150 nm. An appropriate thickness ensures efficient charge collection and discharge, and maintains a good balance between the electrode and the hole layer.
[0056] According to the second aspect of the present application, a method for preparing the porous molecular cage-modified perovskite solar cell is provided, comprising:
[0057] providing a base layer 1;
[0058] Coating an electron transport material on the surface of the base layer 1 to form an electron transport layer 2;
[0059] Mixing the porous molecular cage material and the perovskite precursor solution to form a modified photoactive precursor solution; coating the modified photoactive precursor solution on the surface of the electron transport layer 2 to form a modified photoactive layer 3;
[0060] A hole transport material is coated on the surface of the modified photoactive layer 3 and subjected to an oxidation treatment to form a hole transport layer 4;
[0061] The electrode material is deposited on the surface of the hole transport layer 4 to form the electrode layer 5 .
[0062] This application can effectively improve the interface defects of perovskite and enhance the extraction and transmission efficiency of carriers by adding molecular cage materials to the perovskite precursor solution; the method is simple to operate and can be mass-produced.
[0063] In some embodiments, the concentration of the perovskite precursor solution is (500-800) mg / mL; for example, any value among 500, 520, 550, 580, 600, 620, 650, 680, 700, 720, 750, 780, 800 mg / mL or a range between any two values; for example, (600-700) mg / mL; for example, (620-650) mg / mL; further 640 mg / mL; the molecular cage material is in the perovskite The concentration of the perovskite precursor solution is 0.1 to 1 mg / mL; for example, any value among 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 mg / mL, or any range therebetween, for example, 0.3 to 0.7 mg / mL; another example, 0.4 to 0.6 mg / mL. Furthermore, each milliliter of the modified photoactive precursor solution contains 640 mg of perovskite material and 0.5 mg of porous organic molecular cage material. Controlling the doping concentration of the molecular cage within the above range can effectively passivate defects in the perovskite lattice and promote normal crystallization of the perovskite crystal and uniformity of the film.
[0064] In some embodiments, the molecular formula of the perovskite material in the perovskite precursor solution is ABX3; wherein A is selected from CH3NH3 + 、NH3CH2NH3 + 、C8H9NH3 + 、Cs + , Rb + and K + One or more of; B is selected from Pb 2+ 、Sn 2+ and Ge 2+ At least one of; X is selected from F - 、Cl - Br - and I - At least one of; preferably, A is CH3NH3 + and / or NH3CH2NH3 + ; B is Pb 2+ ; X is 1 - For example, the perovskite precursor solution is a mixture of FAI, MACl, PbI2, and a solvent; the molar ratio of FAI, MACl, and PbI2 is 1:0.05 to 0.15:1; and the solvent is N,N-dimethylformamide. These selected perovskite types and doped organic molecular cages exhibit superior synergy and compatibility, contributing to improved perovskite interface defect mitigation and photovoltaic performance.
[0065] In some embodiments, the hole transport material is at least one of Spiro-OMeTAD, PTAA and nickel oxide; preferably Spiro-OMeTAD; preferably, the hole transport material is also doped with Li-TFSI (lithium bis(trifluoromethane)sulfonyl imide). For example, the concentration of the Spiro-OMeTAD solution is 72.3 mg / mL, dissolved in chlorobenzene (CB), doped with 35 μL / mL of Li-TFSI solution (260 mg / ml, dissolved in acetonitrile) and 30 μL / mL of 4-tBP (to assist dissolution); after filtering the Spiro-OMeTAD solution, it is spin-coated on the photoactive layer at 3000-4000 rpm for 30 seconds without annealing. It should be noted that Spiro-OMeTAD needs to be oxidized to activate its hole transport ability. The spin-coated sample can be placed in a drying cabinet overnight for full oxidation.
[0066] In some embodiments, the conductive material of substrate layer 1 is ITO and / or FTO. The electron transport material is at least one of SnO2, TiO2, and a fullerene derivative, preferably TiO2. The electrode material is at least one of Au, Ag, Cu, and amorphous carbon, preferably Ag. The materials of each of the above thin films individually possess excellent photoelectric properties and stability, and they interact synergistically to improve the photoelectric conversion efficiency of the perovskite cell.
[0067] In some embodiments, the conductive material of the base layer 1 is deposited by magnetron sputtering. The electron transport material is applied by spin coating, with an annealing temperature of 150-200°C. The modified photoactive precursor solution is applied by spin coating, with a spin speed of 3000-5000 rpm, a spin coating time of 30-60 seconds, and an annealing temperature of 80-150°C. The electrode material is deposited by thermal evaporation. The above preparation steps and heating temperature conditions can form a uniform thin film layer, which is beneficial to the optoelectronic performance of each layer.
[0068] According to a third aspect of the present application, an electronic device is provided, comprising a battery; the battery is the above-mentioned porous molecular cage-modified perovskite solar cell or the perovskite solar cell obtained by the above-mentioned preparation method.
[0069] The present application is further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application.
[0070] All raw materials used in the examples of this application are prior art and can be purchased commercially.
[0071] Example 1
[0072] Step S1: depositing a 150 nm thick ITO thin film as a base layer 1 on a cleaned glass substrate by magnetron sputtering; and cleaning the ITO glass substrate with acetone, isopropyl alcohol, and deionized water in sequence to remove impurities and oil stains on the surface.
[0073] Step S2: a TiO2 thin film with a thickness of 30 nm is spin-coated on the surface of the ITO glass substrate as the electron transport layer 2, and annealed at a temperature of 180°C.
[0074] Step S3: HPOC-101 synthesis method: C4RACHO (20 mg) and malonylhydrazide (6.6 mg) were added to DMF (3 mL) to form a mixture; the mixture was sealed in a 10 mL glass vial and heated at 100°C for 12 hours; after the solution evaporated for several hours, bulk crystals of the molecular cage HPOC-101 were obtained.
[0075] FAI, MACl, and PbI2 were weighed in sequence according to a molar ratio of 1.0:0.1:1 and added to a glass bottle. Then, solvent N,N-dimethylformamide (DMF) was added, and a perovskite precursor solution was obtained by ultrasonic dissolution. The prepared solution concentration was 640 mg / mL. The above-synthesized porous organic molecular cage HPOC-101 was doped into the precursor solution at a doping concentration of 0.5 mg / mL to form a modified photoactive precursor solution. The modified photoactive precursor solution was spin-coated on the surface of the above-mentioned electron transport layer 2, with a rotation speed of 4000 rpm and a spin-coating time of 50 s. The obtained product was placed on a heating table for annealing to form a modified photoactive layer 3 with a thickness of 600 nm and an annealing temperature of 120°C.
[0076] Among them, step S4: a certain amount of Spiro-OMeTAD is dissolved in chlorobenzene (CB) to prepare a Spiro-OMeTAD chlorobenzene solution with a concentration of 72.3 mg / mL, and the chlorobenzene solution is doped with 35 μL / mL of Li-TFSI solution (260 mg / ml, dissolved in acetonitrile) and 30 μL / mL of 4-tBP (to assist dissolution). After filtering the Spiro-OMeTAD solution, it is spin-coated on the modified photoactive layer 3 at 4000 rpm for 30 seconds without annealing. The spin-coated sample is placed in a drying cabinet overnight for full oxidation to obtain a hole transport layer 4. After oxidation, the hole transport ability of Spiro-OMeTAD can be activated.
[0077] Step S5: Deposit a layer of silver (Ag) as the electrode layer 5 on the hole transport layer 4 by thermal evaporation technology; the thickness of the electrode layer 5 is controlled to be 100 nm to ensure good electrical contact and collection performance; The structure of the prepared porous molecular cage modified perovskite solar cell is as follows Figure 1 shown.
[0078] Example 2
[0079] Step S1: depositing a 100 nm thick ITO thin film as a base layer 1 on a cleaned glass substrate by magnetron sputtering; cleaning the ITO glass substrate with acetone, isopropyl alcohol and deionized water in sequence to remove impurities and oil stains on the surface.
[0080] Step S2: a TiO2 thin film with a thickness of 10 nm is spin-coated on the surface of the ITO glass substrate as the electron transport layer 2, and annealed at a temperature of 150°C.
[0081] Step S3: FAI, MACl, and PbI2 were weighed in sequence according to a molar ratio of 1.0:0.1:1, added to a glass bottle, and then solvent N,N-dimethylformamide (DMF) was added. The perovskite precursor solution was obtained by ultrasonic dissolution, and the solution concentration was prepared to be 500 mg / mL. The precursor solution was doped with porous organic molecular cage HPOC-101 (the synthesis method of HPOC-101 was the same as in Example 1) with a doping concentration of 0.1 mg / mL to form a modified photoactive precursor solution; the modified photoactive precursor solution was spin-coated on the surface of the above-mentioned electron transport layer 2, the speed was set to 5000 rpm, the spin coating time was 30 s, and the obtained product was placed on a heating table for annealing to form a modified photoactive layer 3 with a thickness of 300 nm and an annealing temperature of 120°C.
[0082] Step S4: A certain amount of Spiro-OMeTAD is dissolved in chlorobenzene (CB) to prepare a Spiro-OMeTAD chlorobenzene solution with a concentration of 72.3 mg / mL. The chlorobenzene solution is doped with 35 μL / mL of Li-TFSI solution (260 mg / ml, dissolved in acetonitrile) and 30 μL / mL of 4-tBP (to assist dissolution). After filtering the Spiro-OMeTAD solution, it is spin-coated on the modified photoactive layer 3 at 4000 rpm for 30 seconds without annealing. The spin-coated sample is placed in a drying cabinet overnight for full oxidation to obtain a hole transport layer 4. After oxidation, the hole transport ability of Spiro-OMeTAD can be activated.
[0083] Step S5: Deposit a layer of silver (Ag) as the electrode layer 5 on the hole transport layer 4 by thermal evaporation technology; the thickness of the electrode layer 5 is controlled to be 20 nm to ensure good electrical contact and collection performance; The structure of the prepared porous molecular cage modified perovskite solar cell is as follows Figure 1 shown.
[0084] Example 3
[0085] Step S1: depositing a 400 nm thick ITO thin film as a base layer 1 on a cleaned glass substrate by magnetron sputtering; cleaning the ITO glass substrate with acetone, isopropyl alcohol and deionized water in sequence to remove impurities and oil stains on the surface.
[0086] Step S2: a TiO2 thin film with a thickness of 40 nm is spin-coated on the surface of the ITO glass substrate as the electron transport layer 2, and annealed at a temperature of 200°C.
[0087] Step S3: FAI, MACl, and PbI2 were weighed in sequence according to a molar ratio of 1.0:0.1:1, added to a glass bottle, and then solvent N,N-dimethylformamide (DMF) was added. The perovskite precursor solution was obtained by ultrasonic dissolution, and the solution concentration was prepared to be 800 mg / mL. The precursor solution was doped with porous organic molecular cage HPOC-101 (the synthesis method of HPOC-101 was the same as in Example 1) with a doping concentration of 1.0 mg / mL to form a modified photoactive precursor solution; the modified photoactive precursor solution was spin-coated on the surface of the above-mentioned electron transport layer 2, the speed was set to 5000 rpm, the spin coating time was 30 s, and the obtained product was placed on a heating table for annealing to form a modified photoactive layer 3 with a thickness of 800 nm and an annealing temperature of 120°C.
[0088] Step S4: A certain amount of Spiro-OMeTAD is dissolved in chlorobenzene (CB) to prepare a Spiro-OMeTAD chlorobenzene solution with a concentration of 72.3 mg / mL. The chlorobenzene solution is doped with 35 μL / mL of Li-TFSI solution (260 mg / ml, dissolved in acetonitrile) and 30 μL / mL of 4-tBP (to assist dissolution). After filtering the Spiro-OMeTAD solution, it is spin-coated on the modified photoactive layer 3 at 4000 rpm for 30 seconds without annealing. The spin-coated sample is placed in a drying cabinet overnight for full oxidation to obtain a hole transport layer 4. After oxidation, the hole transport ability of Spiro-OMeTAD can be activated.
[0089] Step S5: Deposit a layer of silver (Ag) as the electrode layer 5 on the hole transport layer 4 by thermal evaporation technology; the thickness of the electrode layer 5 is controlled to be 300nm to ensure good electrical contact and collection performance; The structure of the prepared porous molecular cage modified perovskite solar cell is as follows Figure 1 shown.
[0090] Example 4
[0091] The difference between Example 4 and Example 1 is that the concentration of the perovskite precursor solution in step S3 is replaced with 600 mg / mL.
[0092] Example 5
[0093] The difference between Example 5 and Example 1 is that the concentration of the perovskite precursor solution in step S3 is replaced with 700 mg / mL.
[0094] Example 6
[0095] The difference between Example 6 and Example 1 is that the concentration of the perovskite precursor solution in step S3 is replaced with 620 mg / mL.
[0096] Example 7
[0097] The difference between Example 7 and Example 1 is that the concentration of the porous organic molecular cage HPOC-101 added to the perovskite precursor solution in step S3 is replaced with 0.3 mg / mL.
[0098] Example 8
[0099] The difference between Example 8 and Example 1 is that the concentration of the porous organic molecular cage HPOC-101 added to the perovskite precursor solution in step S3 is replaced with 0.7 mg / mL.
[0100] Example 9
[0101] The difference between Example 9 and Example 1 is that the porous organic molecular cage added to the perovskite precursor solution in step S3 is replaced by HPOC-103 (the synthesis method of HPOC-103 is the same as that of HPOC-101 in Example 1, except that malonic acid hydrazide is replaced by glutaric acid hydrazide).
[0102] Example 10
[0103] The difference between Example 10 and Example 1 is that the porous organic molecular cage added to the perovskite precursor solution in step S3 is replaced by HPOC-104 (the synthesis method of HPOC-104 is the same as that of HPOC-101 in Example 1, except that malonic acid hydrazide is replaced by adipic acid hydrazide).
[0104] Example 11
[0105] The difference between Example 11 and Example 1 is that the material for preparing the perovskite light-absorbing layer in step S3 is replaced by: FAI, CsCl, PbI2 (molar ratio 1:0.1:1) dissolved in solvent DMF to form a perovskite precursor solution.
[0106] Example 12
[0107] The difference between Example 12 and Example 1 is that the thickness of the modified photoactive layer prepared in step S3 is replaced with 400 nm.
[0108] Comparative Example 1
[0109] The difference between Comparative Example 1 and Example 1 is that in step S3, the perovskite precursor solution is directly spin-coated on the surface of the electron transport layer 2 to form the photoactive layer 3; and the perovskite precursor solution is not doped with porous organic molecular cage material.
[0110] Comparative Example 2
[0111] The difference between Comparative Example 2 and Example 1 is that in step S3, the molecular cage and DMF are first prepared into a 0.5 mg / mL solution, which is spin-coated on the surface of the electron transport layer 2 to form a molecular cage modified layer, and then the perovskite precursor solution of 640 mg / mL is spin-coated on the surface of the above-mentioned molecular cage modified layer to form a photoactive layer 3.
[0112] Comparative Example 3
[0113] The difference between Comparative Example 3 and Example 1 is that in step S3, the HPOC-101 molecular cage and DMF are first prepared into a 0.5 mg / mL solution, which is spin-coated on the surface of the electron transport layer 2 to form a first molecular cage modified layer, and then the perovskite precursor solution 640 mg / mL is spin-coated on the surface of the above-mentioned first molecular cage modified layer to form a photoactive layer 3, and then the above-mentioned HPOC-101 solution is coated on the surface of the photoactive layer 3 for a second time, and after annealing, a second molecular cage modified layer is formed to form a sandwich structure for the perovskite layer.
[0114] Performance testing
[0115] At room temperature, using a 3A solar simulator, at 100mW / cm 2 The photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 1 to 12 and Comparative Examples 1 to 3 was tested under a light intensity of 0.049 cm. 2 The JV performance of Example 1 is as follows Figure 2 As shown, the JV performance of Comparative Example 1 is as follows Figure 3 The test data are shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] It can be seen from the test results in Table 1 that the photoelectric conversion rates of the perovskite solar cells prepared in Examples 1 to 12 of the present application are significantly higher than those in Comparative Examples 1 to 3; it can be seen that the present application can significantly improve the interface defects of the perovskite layer, improve the charge transfer efficiency, and thus improve the photoelectric performance of the cell by modifying the perovskite material by doping a porous organic molecular cage material into the perovskite material.
[0120] Comparative Example 1 is a traditional perovskite photoactive layer. Due to the presence of various types of defects at the interface of this layer, the photoelectric performance is significantly reduced.
[0121] Comparative Example 2 is to coat a layer of organic molecular cage material on the surface of the electron transport layer. Although the modified material is also used, the molecular cage only exists at the interface between the electron transport layer and the perovskite layer. The modification effect is only on the defects at the interface, and the lattice defects of the entire perovskite layer cannot be modified. The effect on improving the photoelectric performance is not obvious.
[0122] In Comparative Example 3, a layer of organic molecular cage material is respectively arranged between the electron transport layer and the perovskite photoactive layer, and between the perovskite photoactive layer and the hole transport layer; although there is one more molecular cage modification layer than in Comparative Example 2, when a solution containing an organic molecular cage (dissolved in DMF) is coated on the perovskite photoactive layer, DMF will dissolve part of the perovskite layer material, which will destroy the performance of the perovskite light-absorbing layer; therefore, in Comparative Example 3, organic cage material layers are prepared at the upper and lower interfaces of the perovskite photoactive layer, and its photoelectric conversion efficiency is worse than that of Comparative Example 2, and even worse than that of Examples 1 to 12 of the present application.
[0123] It should be noted that the terms "first," "second," and the like in the specification and claims of this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or precedence. It should be understood that the terms used in this manner are interchangeable where appropriate, so that the embodiments of the application described herein can, for example, be implemented in an order other than that described herein.
[0124] The above description is merely a preferred embodiment of the present application and is not intended to limit the present application. Various modifications and variations are possible for those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present application shall be included within the scope of protection of the present application.
Claims
1. A porous molecular cage modified perovskite solar cell, characterized in that: The invention comprises a substrate layer (1), an electron transport layer (2), a modified photoactive layer (3), a hole transport layer (4) and an electrode layer (5) which are stacked in sequence; wherein the material of the modified photoactive layer is obtained by modifying a perovskite material by doping a porous molecular cage.
2. The porous molecular cage modified perovskite solar cell according to claim 1, characterized in that: The porous molecular cage is a hydrazone-containing organic molecular cage.
3. The porous molecular cage modified perovskite solar cell according to claim 1 or 2, characterized in that: The porous molecular cage is a lantern-shaped molecular cage formed by self-assembly of formyl calix[4]arene and dihydrazide through hydrazide bonds.
4. The porous molecular cage modified perovskite solar cell according to any one of claims 1 to 3, characterized in that: The porous molecular cage is selected from at least one of HPOC-101, HPOC-102, HPOC-103, HPOC-104, HPOC-201 and HPOC-301.
5. The porous molecular cage modified perovskite solar cell according to any one of claims 1 to 4, characterized in that: The weight doping ratio of the porous molecular cage in the perovskite material is (0.1-1):(500-800); preferably (0.3-0.7): (600~700)。 6. The porous molecular cage modified perovskite solar cell according to any one of claims 1 to 5, characterized in that: The thickness of the modified photoactive layer (3) is 300 to 800 nm, preferably 400 to 700 nm, and more preferably 500 to 600 nm.
7. The porous molecular cage modified perovskite solar cell according to any one of claims 1 to 6, characterized in that: The molecular formula of the material of the modified photoactive layer (3) is ABX3; Wherein, A is selected from CH3NH3 + 、NH3CH2NH3 + 、C8H9NH3 + 、Cs + , Rb + and K + One or more of; B is selected from Pb 2+ 、Sn 2+ and Ge 2+ At least one of; X is selected from F - 、Cl - Br - and I - At least one of; preferably, A is CH3NH3 + and / or NH3CH2NH3 + ; B is Pb 2+ ; X is 1 - .
8. The porous molecular cage modified perovskite solar cell according to any one of claims 1 to 7, characterized in that: The conductive material of the base layer (1) is ITO and / or FTO; And / or, the material of the electron transport layer (2) is at least one of SnO2, TiO2 and fullerene derivatives; preferably TiO2; And / or, the material of the hole transport layer (4) is at least one of Spiro-OMeTAD, PTAA and nickel oxide; preferably Spiro-OMeTAD; And / or, the material of the electrode layer (5) is at least one of Au, Ag, Cu and amorphous carbon; preferably Ag; And / or, the thickness of the base layer (1) is 100 to 400 nm; preferably 250 to 350 nm; And / or, the thickness of the electron transport layer (2) is 10 to 40 nm; preferably 25 to 35 nm; And / or, the thickness of the hole transport layer (4) is 30 to 300 nm; preferably 50 to 200 nm; And / or, the thickness of the electrode layer (5) is 20 to 300 nm; preferably 30 to 200 nm.
9. A method for preparing a porous molecular cage modified perovskite solar cell according to any one of claims 1 to 8, characterized in that: The method comprises: providing a base layer (1); coating an electron transport material on the surface of the base layer (1) to form an electron transport layer (2); Mixing a porous molecular cage material and a perovskite precursor solution to form a modified photoactive precursor solution; coating the modified photoactive precursor solution on the surface of the electron transport layer (2) to form a modified photoactive layer (3); Coating a hole transport material on the surface of the modified photoactive layer (3) and performing an oxidation treatment to form a hole transport layer (4); An electrode material is deposited on the surface of the hole transport layer (4) to form an electrode layer (5).
10. The method for preparing a porous molecular cage modified perovskite solar cell according to claim 9, characterized in that: The concentration of the perovskite precursor solution is (500-800) mg / mL; preferably (600-700) mg / mL; the added concentration of the porous molecular cage material in the perovskite precursor solution is (0.1-1) mg / mL; preferably (0.3-0.7) mg / mL; And / or, the perovskite precursor solution is a mixture of FAI, MACl, PbI2 and a solvent; preferably, the molar ratio of the FAI, MACl and PbI2 is 1:(0.05-0.15):1; and the solvent is N,N-dimethylformamide; and / or, the modified photoactive precursor solution is subjected to a second annealing after coating, wherein the temperature of the second annealing is 80 to 150° C.; And / or, the hole transport material is at least one of Spiro-OMeTAD, PTAA and nickel oxide; preferably Spiro-OMeTAD; preferably, the hole transport material is further doped with Li-TFSI; And / or, the conductive material of the base layer (1) is ITO and / or FTO; And / or, the electron transport material is at least one of SnO2, TiO2 and fullerene derivatives; preferably TiO2; And / or, the electrode material is at least one of Au, Ag, Cu and amorphous carbon; preferably Ag; And / or, the electron transport material is subjected to a first annealing after coating, and the temperature of the first annealing is 150-200°C.